Small duct type intrahepatic cholangiocarcinoma with extensive intraductal extension mimics an intraductal tubulopapillary neoplasm - Mark Fowler; Jeremy D. Ward; Johann D. Hertel; Eizaburo Sasatomi (Elsevier, 2023)
Intrahepatic cholangiocarcinoma (ICCA) is classified into two main subtypes: small duct and large duct types. Small duct ICCAs are typically mass-forming (MF) type, while large duct ICCAs usually present as the periductal-infiltrating (PI) or the intraductal-growing (IG) type. We report an unusual case of small duct ICCA with both MF and IG growth patterns in a male in his early 70s with a 2.4-cm liver mass. Grossly, there was an extensive intraductal lesion and a small MF-type parenchymal nodule. Immunohistochemistry demonstrated the intraductal and invasive components were positive for CK7, CK19, EMA, and NCAM. The intraductal component showed focal immunoreactivity to alpha-fetoprotein and glypican-3, indicating focal hepatocellular differentiation. These features were consistent with small duct ICCA with secondary intraductal extension rather than a pre-existing intraductal tubulopapillary neoplasm (ITPN), demonstrating small duct ICCA can extend into bile duct lumens forming secondary intraductal lesions.